Physical activity on prescription (PAP): Study of efficiency and patients’ experience of the method - Kristjana Pálsdóttir 1984- (2016)
Background: Physical activity on prescription (PAP), with the aim to increase patient’s physical activity and at the same time decrease symptoms or cure disease and decrease drug intake, is a relatively new treatment option in Icelandic health care. Studies have shown physical activity prescriptions to be successful especially by increasing physical activity and making positive changes in health related quality of life. Research is scarce on the Icelandic model of physical activity on prescription but it is essential to investigate the efficiency of the method and the patients’ experience of going through the process. Aim: The overall aim of this study was to investigate the efficiency of physical activity on prescription in Iceland. Further, the aim was to assess participants’ level of physical activity and mental and physical wellbeing before and after their physical activity prescription and also their perceived support during PAP. Methods: A 36 item study-specific questionnaire was created to assess the total experience of going through a physical activity prescription. The internet-based questionnaire was sent with a link with the secure location of the survey to all patients (N=399) receiving physical activity on prescription from March 2013 - May 2014. Descriptive statistics were used to determine the characteristics of the participants. Frequencies and proportions were calculated for all outcomes of interest and further, Chi-square tests were conducted to assess differences between proportions. Results: A total of 169 (42%) answered the questionnaire. The majority of participants (52%) increased their number of weekly physical activity sessions following PAP;; the proportion of participants never or seldom engaging in physical activity decreased from 79% before PAP to 42% after PAP. The proportion of participants experiencing poor mental wellbeing decreased from 47% before PAP to 15% after PAP, while the proportion experiencing poor physical wellbeing remained similar (p=0.67). Participants who were ...